2022
DOI: 10.1002/csc2.20827
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of tillers to maize yield stability at low plant density

Abstract: One of the main challenges of using low plant densities in restrictive and variable environments is to maximize the use of resources in better‐than‐expected years. In this context, tillering could be an alternative to increase reproductive and vegetative plasticity. The objectives of this study were to (a) characterize the correlation between environmental conditions, tiller traits, crop grain yield, and grain yield advantages due to tillers; (b) determine the grain yield response to tillering (i.e., grain yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…There are hybrids that have a tendency to produce more than one ear plant −1 (Tokatlidis & Koutroubas, 2004), but hybrids grown at commercial populations usually produce only one ear (Duvick et al., 2004; Echarte et al., 2000; Motto & Moll, 1983; Tollenaar et al., 1992). Some hybrids produce ear‐bearing tillers at low populations (Massigoge et al., 2022; Rotili et al., 2021; Veenstra et al., 2021) which essentially increases ears plant −1 , but again tillers are usually absent at commercial populations. Producers in the pre‐mechanized era favored single‐ear hybrids (Collins et al., 1965; Crow, 1998) and this preference apparently carried over into the modern era.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are hybrids that have a tendency to produce more than one ear plant −1 (Tokatlidis & Koutroubas, 2004), but hybrids grown at commercial populations usually produce only one ear (Duvick et al., 2004; Echarte et al., 2000; Motto & Moll, 1983; Tollenaar et al., 1992). Some hybrids produce ear‐bearing tillers at low populations (Massigoge et al., 2022; Rotili et al., 2021; Veenstra et al., 2021) which essentially increases ears plant −1 , but again tillers are usually absent at commercial populations. Producers in the pre‐mechanized era favored single‐ear hybrids (Collins et al., 1965; Crow, 1998) and this preference apparently carried over into the modern era.…”
Section: Discussionmentioning
confidence: 99%
“…Flexibility (prolificacy and/or tillering) would de‐couple yield increases from population, making it possible to end the population treadmill. The opportunity to plant at lower populations while retaining the ability to respond to higher‐yielding environments (Massigoge et al., 2022; Rotili et al., 2021; Veenstra et al., 2021) represents another advantage of flexible corn plants.…”
Section: Discussionmentioning
confidence: 99%
“…While continued study is necessary, corn tillers may provide breeders and growers with plasticity trait options to achieve desirable plant density independence in certain environments (Mylonas et al, 2020). By offering additional crop reproductive plasticity when plant-available resources surpass thresholds of selected plant densities, tillers can mitigate management deficits which cannot be remediated mid-season (Rotili et al, 2021;Massigoge et al, 2022). Future work should evaluate tiller development prediction, specifically driving factors of contrasting levels of expression plasticity, in addition to parameters influencing tiller ear development and resulting reproductive efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…While previous field studies have considered corn yield as a response to tiller presence (Sangoi et al, 2009;Frank et al, 2013;Massigoge et al, 2022), efforts to understand the mechanisms and flexibility of observed compensatory relationships are lacking, at least in the US. Considering trends in corn genetic selection and agronomic management in the US, plant density is a historic focal point (Duvick et al, 2004) with highly determinate, hierarchical yield components.…”
Section: Introductionmentioning
confidence: 99%
“…While past work has quantified the impact of tillers on corn yield (Sangoi et al, 2009;Veenstra et al, 2021;Massigoge et al, 2022), plastic capacity (Rotili et al, 2021a;Rotili et al, 2022), and resource use (Thapa et al, 2018;Rotili et al, 2022), no substantial effort has been made to quantify the predictability of corn tiller presence in field scenarios. Corn yields were not reduced, but did respond to varying levels of tiller density (i.e., tillers ha -1 ) in previous work from the available database (Veenstra et al, 2021;Veenstra et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%